Performance of agri-horti-silvi system in the hot arid region of Rajasthan - Singh, Bilas (Indian Journal of Agroforestry, 2020)
The performance influence of a combination of horticulture species (Zizyphus mauritiana, Cordia mixa and Emblica officinalis) and silviculture (Prosopis cineraria, Ailanthus excelsa and Colophospermum mopane) species on wheat (Triticum aestivum L.) yield was studied for five year under supplementary irrigation with a view to enhance land productivity in term of fruit, fodder and food in arid environment of Rajasthan. Horti and silvi species were planted in alternate tree with 9 possible combinations and wheat was intercropped for five years. Survival and collar diameter of trees were greater (P